2001
DOI: 10.1117/1.1412438
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Pachymetry During Photorefractive Keratectomy Using Optical Low-Coherence Reflectometry

Abstract: Optical low-coherence reflectometry (OLCR) was used as a noncontact method to measure the central corneal thickness of three patients intraoperatively during photorefractive keratectomy. Continuous on-line measurements were performed on the intact cornea immediately before the beginning of surgery, after the removal of the corneal epithelium, during laser tissue photoablation, and for 3 min after the ablation process. Corneal thinning due to evaporation was studied on a separate patient with the OLCR instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…In this experimental evaluation with human corneas we observed that the optically measured central ablation depth was significantly higher than the calculated depth. Also with US [12,22] and optically [9,20,37], significantly more tissue was ablated than predicted, which most probably is due to dehydration of the corneal stroma [9,11,30] or other laser-tissue interactions [4,18] occurring during excimer laser ablation. It seems that the effects on corneal tissue from dehydration can be caused from exposure to air with evaporation and consequent thinning, which has been found to be dramatic in some cases, ranging from 10% to 13% in the normal, epithelialized cornea in a 10-min period [10,35] and up to 28.5% after 50-60 min [7,33].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this experimental evaluation with human corneas we observed that the optically measured central ablation depth was significantly higher than the calculated depth. Also with US [12,22] and optically [9,20,37], significantly more tissue was ablated than predicted, which most probably is due to dehydration of the corneal stroma [9,11,30] or other laser-tissue interactions [4,18] occurring during excimer laser ablation. It seems that the effects on corneal tissue from dehydration can be caused from exposure to air with evaporation and consequent thinning, which has been found to be dramatic in some cases, ranging from 10% to 13% in the normal, epithelialized cornea in a 10-min period [10,35] and up to 28.5% after 50-60 min [7,33].…”
Section: Discussionmentioning
confidence: 78%
“…Online OCP revealed itself to be a valuable and reproducible method in this experimental study. Recently, a similar laser-based continuous optical pachymeter integrated in the beam of an excimer laser unit was presented in experimental studies [6,7,8] and for photorefractive keratectomy (PRK) [9]. Also during LASIK intraoperative corneal thickness measurements were possible due to the high optical sensitivity of low-coherence interferometry in low surface reflectivities as well as irregular surfaces [15,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, in this clinical study, a high pulse-to-pulse stability was noted, compared to polymethylmethacrylate (PMMA) ablation studies in corneal tissue, a greater measurement error must be considered [11,12,28], and the measured ablation values were higher than calculated. Also, with intraoperative contact ultrasound [8,13,21,22] and optically [4,26,29,31], significantly more tissue was ablated intraoperatively than predicted. The average differences between the calculated and measured myopic laser resection have been shown to range between 25 and 40 μm [8,22,26,29,31].…”
Section: Discussionmentioning
confidence: 78%
“…This was a significant advantage compared to the proposed use of intraoperative acoustic measurements during LASIK [8,13,18,21,22], since conventional ultrasound technology can only be used intermittently at predetermined time points, has limited resolution, is highly variable, and needs direct contact with the cornea. Early experimental studies with optical systems revealed that an intraoperative measurement of the ablation process in PRK was possible [3,4,9]. This clinical evaluation sought to investigate the intraoperative ablation parameters with online OCP during LASIK to better understand the laser-corneal tissue interactions, and, possibly, determine intraoperative factors capable of predicting the postoperative refraction outcome.…”
Section: Introductionmentioning
confidence: 99%